Effect of Geographic Regions on the Flavor Quality and Non-Volatile Compounds of Chinese Matcha - Hongchun Cui; Yun Zhao; Hongli Li; Min Ye; Jizhong Yu; Jianyong Zhang (Foods)
Matcha is a very popular tea food around the world, being widely used in the food, beverage, health food, and cosmetic industries, among others. At present, matcha shade covering methods, matcha superfine powder processing technology, and digital evaluations of matcha flavor quality are receiving research attention. However, research on the differences in flavor and quality characteristics of matcha from the same tea tree variety from different typical regions in China is relatively weak and urgently required. Taking Japan Shizuoka matcha (R) as a reference, the differences in sensory quality characteristics and non-volatile substances of matcha processed with the same tea variety from different regions in China were analyzed. The samples were China Hangzhou matcha (Z1), China Wuyi matcha (Z2), China Enshi matcha (H), and China Tongren matcha (G), which represent the typical matcha of eastern, central, and western China. A total of 1131 differential metabolites were identified in the matcha samples, comprising 118 flavonoids, 14 tannins, 365 organic acids, 42 phenolic acids, 22 alkaloids, 39 saccharides, 208 amino acids and derivatives, 17 lignans and coumarins, seven quinones, 44 nucleotides and derivatives, 14 glycerophospholipids, two glycolipids, 15 alcohols and amines, 140 benzenes and substituted derivatives, 38 terpenoids, 30 heterocyclic compounds, and 15 lipids. Kaempferol-7-O-rhamnoside, 3,7-Di-O-methylquercetin, epigallocatechin gallate, epicatechin gallate, and epigallocatechin were detected in Z1, Z2, H, and G. A total of 1243 metabolites differed among Z1, Z2, and R. A total of 1617 metabolites differed among G, H, and R. The content of non-volatile difference metabolites of Z2 was higher than that of Z1. The content of non-volatile difference metabolites of G was higher than that of H. The 20 key differential non-volatile metabolites of Z1, Z2, G, and H were screened out separately. The types of non-volatile flavor differential metabolites of G and H were more numerous than those of Z1 and Z2. The metabolic pathways, biosynthesis of secondary metabolites, biosynthesis of co-factors, flavonoid biosynthesis, biosynthesis of amino acids, biosynthesis of various plant secondary metabolites, and purine metabolism of metabolic pathways were the main KEGG pathways. This study provides new insights into the differences in metabolite profiles among typical Chinese matcha geographic regions with the same tea variety.